Phenyl‐γ‐valerolactones and healthy ageing: Linking dietary factors, nutrient biomarkers, metabolic status and inflammation with cognition in older adults (the VALID project). Issue 4 (10th June 2020) - Angelino, D.; Caffrey, A.; Moore, K.; Laird, E.; Moore, A. J.; Gill, C. I. R.; Mena, P.; Westley, K.; Pucci, B.; Boyd, K.; Mullen, B.; McCarroll, K.; et al.
Abstract: Populations globally are ageing, leading to increased prevalence of cognitive dysfunction and dementia. Certain dietary patterns and/or nutritional components may have beneficial effects in helping to prevent or delay the onset of cognitive dysfunction in older adults. Flavan‐3‐ols, a complex subgroup of polyphenols (including catechins and proanthocyanins) which are abundant in foods such as tea, cocoa, grapes, nuts and berries, are almost exclusively metabolised by colonic bacteria to form phenolic acids and phenyl‐γ‐valerolactones (PVLs). PVLs, now thought to exert the anti‐inflammatory and neuroprotective effects originally attributed to flavan‐3‐ols, are relatively stable in plasma and may thus provide reliable biomarkers of dietary exposure to flavan‐3‐ols. In the VALID project (a transnational collaboration involving partners in the UK, Ireland and Italy), we aim to validate plasma PVLs as robust biomarkers of catechin/proanthocyanidin‐rich foods and demonstrate their association with cognitive function in older adults. We will utilise existing data and perform new analysis of samples from the Trinity‐Ulster and Department of Agriculture ( TUDA ) cohort, a study of 5186 older adults providing comprehensive data on a range of relevant variables, including nutrient biomarkers, inflammatory markers, clinical variables, socio‐economic factors and cognitive measures. In addition, we will access samples from TUDA 5+, a follow‐up study of 1000 participants from the original TUDA cohort resampled 5–7 years after their initial investigation, enabling an assessment of cognitive decline. This project aims to validate PVLs as robust biomarkers of dietary polyphenol intake and determine the potential role of catechin/proanthocyanidin‐rich foods in preserving better cognitive heath in ageing.